Riparian forest subsidises the biomass of fish in a recently formed subtropical reservoir. Issue 2 (18th September 2020) - Felden, Juliana; González‐Bergonzoni, Iván; Rauber, Adelita Maria; da Luz Soares, Marlon; Massaro, Marthoni Vinicius; Bastian, Rodrigo; Reynalte‐Tataje, David Augusto
Abstract: Riparian forest may represent a key subsidy to aquatic food webs. While most research has been done in running waters, the origin of resources subsidising biomass and the role of riparian coverage in food webs remains largely unstudied in reservoirs. This research evaluated the role of forest riparian zones as food web subsidies in a recently formed reservoir of Ijuí River, Brazil. The diet of fish and the origin of carbon and nitrogen fuelling fish biomass was compared between littoral habitats with riparian forests and of open canopy. Sampling for stable isotopes of fish and basal resources and the application of bayesian mixing models showed that most of the fish production originates from terrestrial carbon in this recently formed reservoir. Moreover, an increasing terrestrial support to the biomass was found towards the riparian forest areas (subsidising c.a. 70% vs. around 57% of fish biomass in littoral areas of riparian forest and open canopy, respectively).This study remarked the role of riparian forest areas as energetic subsidises to aquatic ecosystems. Management actions in newly formed reservoirs should include preserving riparian forests to avoid losing natural ecosystem subsidies.